Perancangan Sistem Informasi Penjualan Produk UKM Kerajinan Ukir Kaca Sebagai Portal Community Marketing Berbasis Web - Hidayah, Nurul Wahid; , Husni Thamrin, S.T, M.T, Ph.D (2016)
Glass carving craft is one of Small and Medium Enterprises (SMEs) in the region of Solo Raya which has been developing very rapidly since 1995. Considering the development of existing information systems, it is most appropriate to utilize web as a medium to promote a product (E-Commerce).This Research takes a place in Solo Raya region where glass crafting SMEs doesn't have the media to promote its products and to record sales transactions manually. Consumers have to come to the craftsmen workshop or stores directly to get information on products and purchase to order products mirror glass. The research method is SDLC (System Development Life Cycle) in accordance with the waterfall model phases including analysis, design, code generation, testing and support. A questionnaire is setup in order to find out how big the benefits of the system are made. Tests using blackbox testing method. The application is created using PHP and MySQL program, the user interface is HTML and CSS, Google Chrome software, XAMP, Dreamweaver and MySQL database. Based on the results of the study it can be concluded that the application is capable of helping the artisans in promoting their products into the system of the web that has been designed. In addition the system can be an alternative medium of information as well as facilitating buyers in the transaction shopping at "Toko Cermin Online" more effectively so that the purchasing intention of buyers may increase.